Spotlighting the Neglect of Balinese Women's and Children's Rights in Custody Court Decisions - Bunga, Dewi; Segara, I Nyoman Yoga; K. Tus, Desyanti Suka Asih (Udayana Journal of Law and Culture; Vol 8 No 2 (2024)DO - 10.24843/UJLC.2024.v08.i02.p05, 2024)
The Balinese society adheres to a patrilineal kinship system in which men are considered the successors of the lineage. This system often serves as the rationale for awarding child custody to fathers in divorce cases, frequently disregarding the rights of the mother and the best interests of the child. This study examines the implications of the patrilineal kinship system on divorce proceedings, the criteria used by judges in child custody decisions among the Balinese, and the potential for reconstructing child custody arrangements to prioritize the child's best interests. It is a legal research that examines the normative issues regarding child custody in a patrilineal society with a gender perspective. This paper suggests that decisions regarding child custody should refer to the child's best interests principle and gender responsiveness. In the event of a divorce, a wife is typically returned to her parents by her husband's extended family, a process known as “ mulih deha ”, which effectively reverts her to the status of a girl, implying she has no children and does not retain any marital property. Societal culture holds that a child is considered secure in the father's household, even if the paternal grandparents provide care. This entrenched belief system discourages Balinese women from pursuing child custody. A co-parenting model, allowing both parents to remain actively involved, can help reconstruct child custody arrangements to serve the child's best interests better.